Limit theorems for the sums of multidimensional stochastic step processes - Grigelionis, B. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Григелионис. Предельные теоремы для сумм многомерных ступенчатых случайных процессовB. Grigelionis. Daugiamačių laiptuotų atsitiktinių procesų sumų ribinės teoremos